Chrysin protects against kidney tissue oxidative damage caused by pemetrexed used in cancer treatment (Annals of Medical Research, 2023)
Aim: Pemetrexed (PMTX) is a multi-targeted anticancer agent that exerts its antifolate effect by disrupting the folate dependent metabolic processes underlying cell proliferation. Kidney toxicity is a common side effect of anticancer agents. Chrysin (Chr) is a powerful antioxidant compound abundant in plant extracts, honey, and bee propolis. The aim of this study is to investigate the effect of the combined use of chrysin, a natural flavonoid, against the possible harmful effects of PMTX on kidney tissue.Materials and Methods: 50 Wistar albino male rats were divided; Control, Sham, PMTX, Chr, PMTX+Chr groups. Sham (1ml corn oil/day), Chr (50mg/kg/day) by oral gavage, PMTX (1mg/kg/week) by i.p., PMTX+Chr (PMTX;1mg/kg/week, Chr;50mg/kg/day)  were given at the same time every day. At the end of 4 weeks of the study, kidney tissues and blood were collected. Creatinine (Cr) and blood-urea-nitrogen (BUN) analyzed in serum by ELISA. The malondialdehyde (MDA), superoxide dismutase (SOD) activities and total antioxidant status (TAS), total oxidant status (TOS), OSI also were measured in kidney tissue.Results: Indicators of oxidative stress, MDA was elevated and antioxidant activity was reduced in the PMTX groups compared to Control and Sham groups (p
Keywords: Pemetrexed; Chrysin; Kidney; Oxidative Stress; Rat